Comparison of the effect of post-exercise cooling with ice slurry ingestion between males and females. (July 2021) - Iwata, Risa; Kawamura, Takuji; Hosokawa, Yuri; Chang, Lili; Suzuki, Katsuhiko; Muraoka, Isao
Abstract: This study aimed to compare the effects of ice slurry ingestion on post-exercise cooling in males and females. Twenty-four healthy adults (male n = 12; body weight [BW], 65.8 ± 10.3 kg; female, n = 12; BW, 58.2 ± 10.0 kg) participated in this study. Participants ingested 7.5 g/kg of either ice slurry at -1 °C (ICE) or control fluid at 20 °C (CON) during recovery after cycling at 55% VO2max until the rectal temperature reached 38.5 °C or exhaustion in a hot environment (controlled at 38 °C, 40% relative humidity). Rectal (Tre) and skin (Tsk) temperature, ratings of thermal sensation (TS), thermal comfort (TC), heart rate (HR), mean arterial pressure (MAP), and whole body sweat loss (WBSL) were measured 60 min after exercise. Ice slurry ingestion reduced Tre and TS and improved post-exercise hypotension only in females (p < 0.05). In comparison, males did not receive cooling effect from post- exercise cooling with ice slurry ingestion. WBSL tended to be lower in ICE than CON in males (ICE, 454.3 ± 172.3 g; CON, 539.7 ± 157.2 g; p = 0.065). In conclusion, sex differences were observed in the effects of post-exercise cooling with ice slurry ingestion. Highlights: Ice slurry ingestion could decrease rectal temperature and thermal sensation only in females after exercise. Ice slurry ingestion may improve post-exercise hypotension in females. Males did not receive any cooling effect from post-exercise cooling with ice slurry in this study.